PENINGKATAN KUALITAS PEMBELAJARAN IPA MELALUI PENDEKATAN INKUIRI PADA SISWA KELAS IV SDN I MARIBAYA KARANGANYAR PURBALINGGA (Improving the Quality of Teaching Science through Inquiry Approch at the Students of Year IV Maribaya 1 State Primary School, Kar - Sari, Kitri Nur Indah (Jurnal Kreatif : Jurnal Kependidikan Dasar, 2010)
Based on earlier observation on 19 July 2010, it found that the quality of science teaching and learning process at Maribaya 1 state primary school was still low. As a result, the students were less active, and they did not respond to science lesson. The teacher was not active enough in teaching and as the impact of all, students’ science achievement was still not good. The subject of the research were all the students of year IV, Maribaya 1 state primary school, Karanganyar Purbalingga. This was a classroom action research with three cycles, and each cycle consisted of planning, acting, observing and reflecting. The results of the reserach were that the quality of science teaching and learning process improved. The results in details were as follows: (1) during the research process students’ activity improved significantly. At the first cycle the degree of students’ activity was 42.30%, fair qualification; the second cycle was 58.01%, fair qualification; and at the third one was 66.10%, high qualification. The next result was that teacher’s skills in teaching improved. At the first cycle, the teacher got score 27 with good qualification (B), and at the next cycle was 31 with high qualification (A). At the third it improved to be 36, with high qualification (A). The other result of the research were that 71% out of the students responded, 96% students felt happy, 77% students could do presentation, and 81% students looked enthusiastic in learning science. The students got passing grade points 60 at average (33%), at the second cycle, their average point became 6.8 (60%), and at the third one was 71 point at average (75%). Based on the research, it could be concluded that teaching and learning science using inquiry approach could improve students’ activity, teacher’s teaching skills, students; responses, and students’ achievement. Keywords: Science teaching quality, inquiry approach